2006
DOI: 10.1590/s0104-66322006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Parameters optimization for enzymatic assays using experimental design

Abstract: -The conditions for maximization enzymatic activity were determined using experimental design and inulinase from Kluyveromyces marxianus ATCC 16045. The effects of substrate concentration (sucrose and inulin), pH and temperature on inulinase activity were verified using four factorial design and surface response analysis. Using sucrose as substrate. It has bean shown that the effects sucrose on enzymatic activity is not statistically significant and the best condition for the highest activity (110 U/mL) was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…As an illustration, the parameters of the previous study of Burkert et al (2006), who reported adsorption data for inulinase in a stirred tank employing a specific resin, constant pH and temperature, were used to simulate the adsorption of inulinase in an expanded bed under the same conditions (Moraes et al, 2009). The column efficiencies calculated from the model breakthrough curve prediction and from the experimental data were 74.0% and 57.3%, respectively (Moraes et al, 2009).…”
Section: Determination Of Adsorption Isotherms and Kineticsmentioning
confidence: 99%
“…As an illustration, the parameters of the previous study of Burkert et al (2006), who reported adsorption data for inulinase in a stirred tank employing a specific resin, constant pH and temperature, were used to simulate the adsorption of inulinase in an expanded bed under the same conditions (Moraes et al, 2009). The column efficiencies calculated from the model breakthrough curve prediction and from the experimental data were 74.0% and 57.3%, respectively (Moraes et al, 2009).…”
Section: Determination Of Adsorption Isotherms and Kineticsmentioning
confidence: 99%
“…The validation of the model was investigated under the conditions predicted against the responses obtained for enzyme production. A differential correlation was noted between the observed and predicted values as reported by Burkert et al (2006). The optimal levels of the parameters for improved enzyme production under submerged fermentation (SmF) were incubation period (72 h), initial pH (5), CSL 6, yeast extract 9.5, starch 10 and lactose 20 (g/l).…”
Section: Resultsmentioning
confidence: 80%
“…Correspondingly, the lower probability values indicated that the model terms are statistically valid. The analysis of linear, quadratic and interaction coefficients were performed on the batch culture results which highlighted that enzyme production was a function of the independent parameters (Ahuja et al 2004) Lactose used as a sole carbon source (degree of freedom 3) has an important physiological role in the improvement of enzyme activity (Burkert et al 2006). According to these results, the fungal strain of A. oryzae IIB-6 could be considered as an organism of choice for GGH productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Optimization studies are carried out using response surface methodology (RSM) which is a mathematical and statistical technique widely used to determine the effects of several variables and their interactions and to optimize different biotechnological processes (Oprime and Suazo, 1997;Burkert et al, 2006;Zafar et al, 2010;Coelho et al, 2011;). RSM has been extensively applied to optimize culture medium and other process parameters for the production of β-fructofuranosidase (Chen 1998), lipase (He and Tan 2006;Liu et al, 2006), tannase (Battestin and Macedo 2007), α-amylase (Rao and Satyanarayana 2007), α-cyclodextrin glucanotransferase (Ibrahim et al, 2005), dextran dextrinase (Naessens et al, 2004) and chitinase (Nawani and Kapadnis 2005).…”
Section: Introductionmentioning
confidence: 99%